Revitalisasi Ekstrakurikuler di Madrasah Aliyah Assulaimaniyah Dukuhmojo melalui Pelatihan Seni Kaligrafi - Wisnu Siwi Satiti; Ali Mashari; Fitri Umardiyah; Auliyatul Latifah; Farda Aulisna Permana Putri; Miftahul Janah; Layla Dewi Safitri; Yuhyil Ayda Rahma (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2023)
School extracurricular activities are one of the core activities of students in addition to teaching and learning activities. Based on the results of observations and interviews with teachers and students at MA Assulaimaniyah Dukuhmojo, it is known that extracurricular activities at school are still limited. Especially arts extracurriculars, there are still none at senior high school MA Assulaimaniyah Dukuhmojo. One of the extracurricular arts that many people are interested in but have not yet socialized optimally is the art of calligraphy. MA Assulaimaniyah is based on an Islamic foundation. This is an opportunity to carry out socialization and training in the art of calligraphy at MA Assulaimaniyah, Dukuhmojo village. Thus, in this service, calligraphy art training activities were carried out for MA Assulaimaniyah students in Dukuhmojo village. This service activity adopts the Participatory Action Research (PAR) method. The results of this community service show that training activities can increase students' insight and knowledge about the art of calligraphy. Apart from that, this training activity is effective in increasing students' motivation and desire to learn and practice calligraphy art skills. This calligraphy art training activity also adds to the variety of extracurricular activities at MA Assulaimaniyah, Dukuhmojo village, Mojoagung District, Jombang Regency.